2020
DOI: 10.1186/s12913-020-5018-9
|View full text |Cite
|
Sign up to set email alerts
|

“We’ve got the home care data, what do we do with it?”: understanding data use in decision making and quality improvement

Abstract: Background: In the past decade the provision of home care services in Canada has doubled; with this increase there has been a growing interest in improving quality and safety. National-level data are captured in the Home Care Reporting System (HCRS), using the interRAI-HC tools. Data in the HCRS provide decision-makers and administrators with actionable evidence to inform quality and safety improvement initiatives. The objective of this study was to determine how providers and administrators were using these d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 12 publications
(12 reference statements)
0
9
0
1
Order By: Relevance
“…A recent Canadian study reported the use of quality indicator data to guide patient safety and quality improvement initiatives, specifically in the areas of antipsychotic use, management of pain and falls mitigation strategies. 21 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A recent Canadian study reported the use of quality indicator data to guide patient safety and quality improvement initiatives, specifically in the areas of antipsychotic use, management of pain and falls mitigation strategies. 21 …”
Section: Discussionmentioning
confidence: 99%
“…25 This lack of discrimination between types of home care services provided and implementation of home care quality indicators may, in part, be attributable to some of the identified barriers to optimal utilisation internationally. 21 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, as the overall structure of the Ontario home care system has remained largely unchanged since that time, the findings are believed to be relevant to current care practices. A recent study on the use of home care assessment data in the home care sector confirms this relevance, indicating that these data are both undervalued and underutilized for evidence-informed decision-making across the sector [ 74 ].…”
Section: Discussionmentioning
confidence: 99%